Relationship between Weight, Body Mass Index, and Bone Mineral Density in Men Referred for Dual-Energy X-Ray Absorptiometry Scan in Isfahan, Iran - Mohammad Reza Salamat; Amir Hossein Salamat; Iraj Abedi; Mohsen Janghorbani (Journal of Osteoporosis)
Objective. Although several studies have investigated the association between body mass index (BMI) and bone mineral density (BMD), the results are inconsistent. The aim of this study was to further investigate the relation between BMI, weight and BMD in an Iranian men population. Methods. A total of 230 men 50-79 years old were examined. All men underwent a standard BMD scans of hip (total hip, femoral neck, trochanter, and femoral shaft) and lumbar vertebrae (L2-L4) using a Dual-Energy X-ray Absorptiometry (DXA) scan and examination of body size. Participants were categorised in two BMI group: normal weight <25.0 kg/m2 and overweight and obese, BMI ≥ 25 kg/m2. Results. Compared to men with BMI ≥ 25, the age-adjusted odds ratio of osteopenia was 2.2 (95% CI 0.85, 5.93) and for osteoporosis was 4.4 (1.51, 12.87) for men with BMI < 25. It was noted that BMI and weight was associated with a high BMD, compatible with a diagnosis of osteoporosis. Conclusions. These data indicate that both BMI and weight are associated with BMD of hip and vertebrae and overweight and obesity decreased the risk for osteoporosis. The results of this study highlight the need for osteoporosis prevention strategies in elderly men as well as postmenopausal women.